Changes of membrane fatty acids of salmonella enteritidis treated with the essential oil of satureja hortensis - Kotan, Recep; Dikbas, Neslihan; Tozlu, Elif; Bagci, Eyüp (My University, 2012)
There are many studies focused on antibacterial and antifungal activity of the essential oil or extracts of Satureja hortensis. But their modes of action against microorganisms are poorly understood. The first objective of this study was to determine the antibacterial activity of Satureja hortensis essential oil (500 ?l/ml) against Salmonella enteritidis strains on the growing media (Triptic Soy Agar) at 35 °C. The second objective was to determine the effect of the oil on the fatty acid composition of the bacterium to identify the mechanism of antimicrobial action. Antibacterial activity assays were carried out by disc diffusion method. Analyses of the fatty acid compositions were performed according to the method described by the manufacturer's manual (Sherlock Microbial Identification System, MIDI, Inc.,.Newark, DE, USA). For fatty acid analysis, the essential oil (60 ?l/ml) was added to bacterial strain inoculations, simultaneously and after 24-h bacterial inoculation in the growing media (Triptic Soy Broth). Our results showed that the essential oil of Satureja hortensis has a stronger antibacterial activity than that of Streptomycin antibiotic against Salmonella enteritidis. In addition, it was observed that the proportion of the total saturated fatty acids increased in the Salmonella enteritidis cells, induced by addition of this oil in the growing media of both applications. But, the proportion of the total unsaturated fatty acids decreased. The changes were observed especially on decreasing of the proportion of the long-chain saturated fatty acids. To the best of our knowledge, this is the first study about the modes of actions and antimicrobial effect mechanisms of the essential oil of S. hortensis. © by PSP.
Keywords: Antibacterial activity; Essential oil; Fatty acid; Salmonella enteritidis; Satureja hortensis